PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA UNTUK PROYEKTOR DI RUANG A102 FAKULTAS TEKNIK UNIVERSITAS RIAU KEPULAUAN - Pamor Gunoto; Demontri Darmayanti (SIGMA TEKNIKA, 2019)
In the midst of globalization, energy is a major need in people's lives. These energies are used for various purposes, namely for industry, vehicles, power plants, fuel, and others. The use of electrical energy at the Riau Kepulauan University is mostly used as a teaching and learning aid. One of the tools used is projector as the main tool for delivering material to students. Due to frequent power outages in the city of Batam, it has an impact on the learning and teaching process, especially in the delivery of lecture material for students. The design of Solar Power Plants (PLTS) discusses to the power supply backup if a power outage occur so that the learning and teaching process can still continues. After testing and retrieval of data on this PLTS, the results obtained on average are 16.6 watt and the power supply backup electricity on projector last for 47 minutes.